The Campaign of the Solomonic Monarch Yǝsḥaq (r. 1414–1429/30) as a Turning Point in Betä Ǝsraʾel History: Its Commemoration in Solomonic and Betä Ǝsraʾʾel Sources and Holy Sites - Kribus, Bar (Aethiopica, 2023)
Following the rise to power of the Christian Solomonic dynasty (1270–1974) in Ethiopia, Christian rule expanded to encompass the regions inhabited by the Betä Ǝsraʾʾel (Ethiopian Jews). This process was accompanied by military campaigns (fourteenth–seventeenth century), during which the Betä Ǝsraʾʾel gradually lost their political autonomy. The Betä Ǝsraʾʾel oral tradition remembers the campaign waged by the Solomonic monarch Yəsḥaq against them as the most decisive in their history—because of it, their political power was greatly reduced, and their continued existence was jeopardized. This campaign is also commemorated in Solomonic texts, and both Christian and Betä Ǝsraʾʾel holy sites are associated with it. This article will examine the ways in which this campaign and its aftermath are depicted by the two respective communities and reflected their religious sites and in landmarks in Wägära and the Sǝmen Mountains. Based on the sources at hand, it will attempt to trace the geographical aspects of the campaign.